Intakes of Unprocessed and Minimally Processed and Ultraprocessed Food Are Associated with Diet Quality in Female and Male Health Professionals in the United States: A Prospective Analysis - Rossato, Sinara Laurini; Khandpur, Neha; Lo, Chun-Han; Jezus Castro, Stela Maris; Drouin-Chartier, Jean Philippe; Sampson, Laura; Yuan, Changzheng; Murta-Nascimento, Cristiane [UNESP]; Carvalhaes, Maria Antonieta [UNESP]; Monteiro, Carlos Augusto; Sun, Qi; Fung, Teresa T.; et al. (Elsevier, 2023)
Background: High unprocessed and minimally processed food (UMP) intake has been associated with high-quality diets, whereas the opposite has been shown for ultraprocessed food (UPF). Nevertheless, the association between UMP and UPF consumption and diet quality over the long-term warrants further examination. Objective: This study aimed to assess whether UMP and UPF intake are associated with three diet-quality metrics in female and male health professionals from two US cohorts over 3 decades of follow-up. Design: This was a cohort study, including data from the Nurses’ Health Study (NHS), from 1986 to 2010 (N = 51,956) and the Health Professionals Follow-up Study (HPFS) from 1986 to 2006 (n = 31,307). Participants and setting: Participants were invited in 1976 (NHS) and 1986 (HPFS) to respond to mailed questionnaires every 2 to 4 years and diet was assessed with a semi-quantitative food frequency questionnaire every 4 years. Main exposure measures: UMP and UPF intake were calculated using the NOVA classification. Statistical analyses: Generalized estimating equations for marginal means and repeated cross-sectional associations between diet-quality metrics and quintiles of UMP and UPF. Diets were assessed every 4 years from 1986 to 2010. Results: With increasing quintiles of UMP intakes, the Alternate Healthy Eating Index-2010 increased 7.1% (3.80 points, 95% CI 3.66 to 3.93) in the NHS and 10.1% (5.75 points, 95% CI 5.52 to 5.98) in the HPFS; the Mediterranean diet index increased 11.7% (0.50 points, 95% CI 0.47 to 0.52) in the NHS and 14.0% (0.64 points, 95% CI 0.60 to 0.68) in the HPFS; and the Dietary Approaches To Stop Hypertension diet score increased 7.5% (1.81 points, 95% CI 1.76 to 1.87) in the NHS and 10.6% (2.66 points, 95% CI 2.57 to 2.76) in the HPFS. In the fifth quintile of UPF intake compared with the first, the Alternate Healthy Eating Index-2010 was –9.3% (–4.60 points, 95% CI –4.73 to –4.47) lower in the NHS and –13.7% (–6.89 points, 95% CI –7.12 to –6.66) lower in the HPFS; the Mediterranean diet index was –14.7% (–0.55 points, 95% CI –0.57 to –0.53) lower in the NHS, and –19.0% (–0.74 points, 95% CI –0.78 to –0.70) lower in the HPFS; and the Dietary Approaches To Stop Hypertension diet score was –8.1% (–1.81 points, 95% CI –1.86 to –1.76) lower in the NHS and –12.8% (–2.84 points, 95% CI –2.93 to –2.74) lower in the HPFS. Conclusions: Consumption of UMP was associated with better dietary quality, whereas consumption of UPF was associated with poorer dietary quality.
Keywords: AHEI-2010; DASH diet; Diet quality; Health Professional Follow-up Study; Mediterranean diet; NOVA; Nurses’ Health Study; Ultraprocessed food